Early intervention services for special needs children: An exploration of the effectiveness of early special education in Malaysia - Elaine Hui Fern Tan; Zhooriyati Sehu Mohamad (Psychological Research and Intervention, 2019)
Early intervention programme (EIP) are a range of different programmes included different types of therapy and education that aimed to help and support children with developmental delays or other specific health conditions. The programmes are helpful to improve children development and adaptability, enhance family capability in handling the special needs children and increase family and children participation in society. This research aims to discover the effectiveness and importance of the early special education in Malaysia. To meet the objectives of this study, a qualitative research using phenomenological approach has conducted on five special needs teachers who work in a Non-Governmental Organization (NGO) early intervention centre in Johor, Malaysia by using purposive sampling. Thematic analysis was used to analyse the collected data. This research found that improvement in attention and behaviours, self-care skills, social interaction skills of special needs children are the effectiveness of early intervention services. Besides that, providing knowledge and happiness to the parents and preparing for integration into kindergarten and future schooling are also some of the effectiveness. The implications of this study consist of contributing significantly to the community by making people understand the effectiveness and importance of sending special needs children to the EIP. It is important for the parents to realise the importance of sending their special needs children to the EIP as earlier as possible as learning occur effective before six years old and behavior more likely to be trained. Keywords: early intervention services, early special education, special needs children